Ordered Liberty: Rights, Responsibilities, and Virtues - James E. Fleming, Linda C. McClain (Harvard University Press, 2013)
In recent years, communitarian, civic republican, and progressive thinkers and politicians have argued that our constitutional system takes individual rights too seriously, to the neglect of responsibilities, virtues, and the common good. â€œNo rights without responsibilities,â€ a slogan of Third Way thought, encapsulates this perceived imbalance.1 Similarly, President Barack Obama in his inaugural address called for a â€œnew era of responsibility.â€2 Liberal theories of rights, critics argue, exalt rights over responsibilities, licensing irresponsible conduct and spawning frivolous assertions of rights at the expense of encouraging personal responsibility and responsibility to community. These theories, critics say, require neutrality among competing conceptions of the good life, undermining civil society as â€œseedbeds of virtueâ€ and precluding government from promoting good lives. Worse yet, liberal theories justify rights of autonomy on the ground of â€œemptyâ€ toleration of wrong conduct instead of respect for the personal capacity for responsibility or recognition of the substantive moral goods or virtues promoted by protecting such rights. Finally, liberal theories take rights too absolutely, to the subordination of responsibilities, virtues, and the common good, and in doing so debilitate the political processes and impoverish judgment. Ronald Dworkinâ€™s famous book, Taking Rights Seriously, with his idea of rights as â€œtrumps,â€3 is the bÃªte noire of proponents of such charges of irresponsibility, neutrality, wrongness, and absoluteness. Liberalism, critics claim, promotes â€œliberty as licenseâ€ rather than securing â€œordered liberty This book answers these charges against liberal theories of rights. We propose an account of rights that (1) takes responsibilities as well as rights seriously, permitting government to encourage responsibility in the exercise of rights but not to compel what it holds is the responsible decision; (2) supports what we, following Michael Sandel, call a â€œformative projectâ€4 of civil society and government promoting responsibility, inculcating civic virtue, fostering citizensâ€™ capacities for democratic and personal self-government, and securing ordered liberty and equal citizenship for all; (3) justifies rights of autonomy on the basis not of â€œemptyâ€ toleration, but of toleration as respect, together with the capacity for responsibility and the substantive moral goods furthered by securing such rights; and (4) protects basic liberties (such as freedom of association and rights of autonomy) stringently but not absolutely, through reasoned judgment concerning ordered liberty without precluding government from encouraging responsibility or inculcating civic virtues. We develop an account of responsibility that takes rights seriously, avoids submerging the individual into the community, and appreciates the value of diversity in our morally pluralistic constitutional democracy. We defend our understanding of the relationships among rights, responsibilities, and virtues by applying it to several matters of current controversy: reproductive freedom, the proper roles and regulation of civil society and the family, education of children, clashes between First Amendment freedoms (of association and religion) and antidiscrimination law, and rights to intimate association and same-sex marriage.